Hypotony maculopathy after glaucoma surgery: pathogenic mechanisms, diagnostic tools, and treatment modalites - V.P. Erichev; S.Yu. Petrov; N.A. Orekhova; L.Kh. El’murzaeva (РМЖ "Клиническая офтальмология")
V.P. Erichev, S.Yu. Petrov, N.A. Orekhova, L.Kh. El’murzaeva Scientific Research Institute of Eye Diseases, Moscow, Russian Federation This article reviews risk factors, mechanisms of the development, key diagnostic tools, therapeutic and preventive modalities for hypotony maculopathy. Hypotony maculopathy is a rare complication whose rate has increased after wide adoption of glaucoma surgery. Risk factors for hypotony maculopathy are younger age, male sex, myopia, and primary glaucoma surgery using antimetabolites. Major diagnostic tools for hypotony maculopathy to assess the abnormalities and their changes over time are ultrasound (to provide differential diagnosis in poor fundus visualization), fluorescent angiography (to identify choroidal folds and to differentiate between choroidal and retinal folds), and optical coherence tomography. Therapeutic modalities include conservative methods (i.e., bandage contact lenses to prevent excessive filtration, compressive conjunctival sutures) and surgical procedures (i.e., scleral flap revision, intracameral gas injection, vitrectomy using perfluorocarbon gas, fistula plugging followed by trabeculectomy ab interno). Early and correct identification of the cause of hypotony guarantees treatment success. Keywords: glaucoma, hypotony maculopathy, fistulizing glaucoma surgery, antimetabolites, needling, diagnostics. For citation: Erichev V.P., Petrov S.Yu., Orekhova N.A., El’murzaeva L.Kh. Hypotony maculopathy after glaucoma surgery: pathogenic mechanisms, diagnostic tools, and treatment modalites. Russian Journal of Clinical Ophthalmology. 2020;20(1):–31. DOI: 10.32364/2311-7729-2020-20-1-26-31.